2019
DOI: 10.1088/1742-6596/1279/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Voltammetry Stufy And Electrochemical Synthesis Of Some Organotellurium Compounds

Abstract: The electrochemical behavior of diphenyl ditelluride, bis(2-amino-5-methyl phenyl)ditelluride and bis(2-amino-5-bromo phenyl)ditellurid have been investigated by cyclic voltammetry(CV) in methanol or THF at room temperature. The results showed two single successive electron transfer through the reduction process. This technique was used to determine the best voltage regions in order to carry out the electrochemical synthesis of unsymmetrical organic telluride, i.e : ethyl phenyl telluride (1), propyl phenyl te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In recent years, there has been great interest in studying organo-tellurium compounds containing azomethane group due to the high stability and various applications of these compounds [3,4]. The applications of organotellurium compounds have been reported in several fields [4][5][6][7][8]. Past research reported using organotellurium compounds as antioxidant agents [5,9,10], polymerization catalysts [11][12][13], antitumor and pharmaceutical agents [5,14,15], organic superconductors [3,7], synthetic intermediate [4], and ligands with many transition metal ions [3,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been great interest in studying organo-tellurium compounds containing azomethane group due to the high stability and various applications of these compounds [3,4]. The applications of organotellurium compounds have been reported in several fields [4][5][6][7][8]. Past research reported using organotellurium compounds as antioxidant agents [5,9,10], polymerization catalysts [11][12][13], antitumor and pharmaceutical agents [5,14,15], organic superconductors [3,7], synthetic intermediate [4], and ligands with many transition metal ions [3,16,17].…”
Section: Introductionmentioning
confidence: 99%